2019
DOI: 10.35794/jpekd.17665.19.4.2017
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Investasi, Tenaga Kerja Dan Tingkat Pendidikan Terhadap Pertumbuhan Ekonomi Dan Dampaknya Terhadap Kemiskinan Di Propinsi Sulawesi Utara

Abstract: ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh jumlah investasi (PMDN dan PMA), jumlah tenaga kerja dan tingkat pendidikan, terhadap pertumbuhan ekonomi dan dampaknya terhadap kemiskinan di Sulawesi Utara. Adapun data yang digunakan penulis dalam penelitian ini adalah data sekunder berjenis time series sejak tahun 2003 hingga tahun 2015 yang diperoleh dari Badan Pusat Statistik Sulawesi Utara.Metode yang digunakan dalam penelitian ini adalah Analisis Path. Hasil analisis menunjukkan investasi memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…This is in line with the findings of a previous study that investment has a positive but insignificant influence on poverty (Tamrin, Iskandar, &Effendi, 2022). Another study also showed that it does not have a significant effect on poverty through economic growth (R. Pratama et al, 2017). It is important to note that investment is not only to maximize output but also to determine labor and income distribution, population growth, quality, and technology (Sukirno, 2005)…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of a previous study that investment has a positive but insignificant influence on poverty (Tamrin, Iskandar, &Effendi, 2022). Another study also showed that it does not have a significant effect on poverty through economic growth (R. Pratama et al, 2017). It is important to note that investment is not only to maximize output but also to determine labor and income distribution, population growth, quality, and technology (Sukirno, 2005)…”
Section: Discussionmentioning
confidence: 99%
“…One of several indicators of the total workforce that represents the size of the economically active working-age population is through the use of data on Labor Force Participation figures. Research by Pratama et al (2019) and Barimbing (2015), which claims that the total workforce has a favorable impact on economic growth, supports this.…”
Section: The Relationship Of Labor To Economic Growthmentioning
confidence: 92%
“…Kemiskinan tidak hanya diartikan sebagai ketidakmampuan dalam ekonomi, akan tetapi juga mengenai kegagalan dalam memenuhi hak-hak dasar dalam bermasyarakat (Suryani, 2023). Kemiskinan tentunya dihadapi oleh setiap negara yang diiringi dengan laju pertumbuhan penduduk yang kemudian akan menghasilkan pengangguran, ketimpangan pada pendistribusian pendapatan nasional ataupun pembangunan, dan pendidikan juga menjadi faktor penting dalam persaingan dunia kerja (Pratama et al, 2019).…”
Section: Pendahuluanunclassified